2023
DOI: 10.1097/mop.0000000000001309
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of social care in reducing childhood obesity

Evianna Cruz Herrera,
Amanda I. Figueroa-Nieves,
Jennifer A. Woo Baidal

Abstract: Purpose of review This review evaluates the current evidence for relationships of social factors with childhood obesity and for a role of social care in reduction of childhood obesity. Recent findings Most literature on the relationship between social factors and childhood obesity has examined food insecurity as a risk factor for obesity. Associations between food insecurity and excess weight in children are most consistent during infancy and among thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…HFI is a strong predictor of childhood malnutrition due to its close connection with the accessibility and quality of food in a household. Various studies have also found that food insecurity can contribute to both underweight and overweight among young people, making it a potential barrier to preventing and treating obesity ( 7–9 ).…”
Section: Introductionmentioning
confidence: 99%
“…HFI is a strong predictor of childhood malnutrition due to its close connection with the accessibility and quality of food in a household. Various studies have also found that food insecurity can contribute to both underweight and overweight among young people, making it a potential barrier to preventing and treating obesity ( 7–9 ).…”
Section: Introductionmentioning
confidence: 99%
“…This means acknowledging that neighborhoods bring to bear different opportunities for children to be healthy, as Baker-Smith and Ikomi highlight [10]. Because of this, Woo Baidal [11], Martinez [12], and their colleagues underscore how critical it is to identify underlying social needs and understand cultural practices of families as part of pediatric obesity care. With this understanding, we can address needs like food insecurity that impact a family's ability to live healthfully, tailor interventions to be culturally sensitive, and partner with community stakeholders like schools to increase access to care, as proposed by Essel [13], Wood [14], and their colleagues.…”
mentioning
confidence: 99%